'If and when?': the beliefs and experiences of community living staff in supporting older people with intellectual disability to know about dying. (14th September 2012) - Wiese, M.; Dew, A.; Stancliffe, R. J.; Howarth, G.; Balandin, S.
Abstract: Background The aim of this study was to explore the way in which community living staff engaged with people with intellectual disability (ID) about dying and death. Method Guided by grounded theory methodology, focus groups and individual interviews were conducted with staff who had either no experience with client death, experience of a client sudden death, or a client death experience which was pre‐dated by a period of end‐of‐life care. Results While in principle, staff unanimously supported the belief that people with ID should know about dying, there was limited in‐practice engagement with clients about the topic. Engagement varied according to staff experience, client capacity to understand and the nature of the 'opportunity' to engage. Four 'opportunities' were identified: 'when family die', 'incidental opportunities', 'when clients live with someone who is dying' and 'when a client is dying'. Despite limited engagement by staff, people with ID are regularly exposed to dying and death. Conclusions People with ID have a fundamental right to know about dying and death. Sophisticated staff skills are required to ensure that people with ID can meaningfully engage with end‐of‐life issues as opportunities arise.